2006
DOI: 10.1007/s00240-006-0046-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the efficiency of extracorporeal shockwave lithotripsy for stones in renal units with impaired function: a prospective controlled study

Abstract: The objective was to determine the efficiency of extracorporeal shockwave lithotripsy (ESWL) in clearing stones from renal units with impaired function. Thirty-five patients with poorly functioning kidneys determined by intravenous urogram and 99mtechnetium diethylene triamine pentacetic acid renal dynamic scan underwent ESWL. Stone clearance was assessed at 3 months and compared with that in normally functioning kidneys. The study group was divided into two subgroups. Those with split glomerular filtration ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In published series, the stone-free rate after SWL is considered the main end point of all the experiences, without concern about renal function that can be adversely affected by hydronephrosis. Srivastava et al [13] described the role of ESWL in renal units with impaired function, concluding that SWL outcomes are comparable with those found in normal renal units.…”
Section: Discussionmentioning
confidence: 79%
“…In published series, the stone-free rate after SWL is considered the main end point of all the experiences, without concern about renal function that can be adversely affected by hydronephrosis. Srivastava et al [13] described the role of ESWL in renal units with impaired function, concluding that SWL outcomes are comparable with those found in normal renal units.…”
Section: Discussionmentioning
confidence: 79%
“…Fernandez Rodriguez et al [9] performed a multivariate analysis of 698 randomly selected patients who underwent SWL; the success rate decreased significantly with reduced GFR. Lee et al [5] and Srivastava et al [6] found that SWL is less successful in patients with decreased renal function. Schwartz et al [7] showed that body position has a significant effect on renal perfusion measured by nuclear renal scintigraphy.…”
Section: Discussionmentioning
confidence: 99%
“…The overall success rate of SWL was 88.3% (77. 4 [5] demonstrated that adequate urine production is essential for stone clearance after SWL and that the efficacy of SWL is compromised in patients with renal insufficiency and high creatinine [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In RIRS procedure, the stones are divided into small pieces by laser aiming to take advantage of spontaneous drainage with diuresis that helps stone free state of kidney (3). Various studies in the literature indicate the importance of diuresis for the drainage of fragments after SWL (4,5). According to the study of Koc et al, measurement of renal parenchyma thickness (RPT) is a cost-effective method that can be easily performed on routinely applied non-contrast computerized tomography (CT) and may have predictive value for the surgical success in patients with nephrolithiasis.…”
Section: Introductionmentioning
confidence: 99%